2004
DOI: 10.1207/s15327655jchn2102_01
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat Consumption, Readiness to Change, and Ethnocultural Association in Midlife African American Women

Abstract: Cardiovascular disease (CVD) is the number 1 killer of American women, with African American women disproportionately represented. Dietary fat consumption is a major risk factor for the development of CVD. This study examined the average daily diet of urban midlife African American women, specifically the relation between dietary fat, readiness to change, ethnocultural association, and selected sociodemographic variables. Three hundred days of dietary data were collected. Sixty five percent of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…10 Robinson and Hunter reported that the contributions of total fat and saturated fat to total energy consumption were high among urban African Americans (42.7% and 14.6%, respectively). 11 Kristal and colleagues reported that fat-related behaviors and sources of fat were different for African Americans than for Caucasians, with African Americans consuming more fat from meats than dairy.…”
Section: Food-related Behaviors and Psychosocial Factors Among Africamentioning
confidence: 99%
See 1 more Smart Citation
“…10 Robinson and Hunter reported that the contributions of total fat and saturated fat to total energy consumption were high among urban African Americans (42.7% and 14.6%, respectively). 11 Kristal and colleagues reported that fat-related behaviors and sources of fat were different for African Americans than for Caucasians, with African Americans consuming more fat from meats than dairy.…”
Section: Food-related Behaviors and Psychosocial Factors Among Africamentioning
confidence: 99%
“…However, some studies do show a relationship between food insecurity and increased body weight in women. 5 In 2006, 10.9% of all households in the United States were food insecure, with food insecurity being highest at 21.8% for African Americans. 6 The risk of obesity was reported to be almost 3 times higher among women from Asian, African American, and Hispanic communities experiencing food insecurity with hunger.…”
Section: Introductionmentioning
confidence: 99%
“…These areas have few supermarkets, but do have many small food sources including corner stores, carry-out restaurants, and fast food restaurants [1315]. Corner stores in Baltimore have limited space and stock primarily high fat and high added sugar items [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also found that Black Americans including women have higher fat intakes than Hispanics and Non-Hispanic whites 5, 6, 8, 9, 23, 24. Some of the prevalent fat-related behaviors in SisterTalk were also consistent with previous studies including eating the skin on chicken, frying chicken and fish,8, 9, 24, 25 and a low prevalence of fat lowering behaviors such as: eating meatless meals, eating lower fat cakes and cookies, using low fat food preparation methods 8, 9, 24 .…”
Section: Discussionmentioning
confidence: 91%